Perceived safety in human–cobot interaction for fixed-path and real-time motion planning algorithms - Inara Tusseyeva; Artemiy Oleinikov; Anara Sandygulova; Matteo Rubagotti (Scientific Reports, 2022)
Abstract This study investigates how different motion planning algorithms, implemented on a collaborative robot (cobot), are perceived by 48 human subjects. The four implemented algorithms ensure human safety based on the concept of speed and separation monitoring, but differ based on the following characteristics: (a) the cobot motion happens either along a fixed path or with a trajectory that is continuously planned in real time via nonlinear model predictive control, to increase cobot productivity; (b) the cobot speed is further reduced—or not—in real time based on heart rate measurements, to increase perceived safety. We conclude that (1) using a fixed path—compared to real-time motion planning—may reduce productivity and, at least when heart rate measurements are not used to modify the cobot speed, increases perceived safety; (2) reducing cobot speed based on heart rate measurements reduces productivity but does not improve perceived safety; (3) perceived safety is positively affected by habituation during the experiment, and unaffected by previous experience.